Defining cardiovascular toxicities of cancer therapies: an International Cardio-Oncology Society (IC-OS) consensus statement. (14th December 2021) - Herrmann, Joerg; Lenihan, Daniel; Armenian, Saro; Barac, Ana; Blaes, Anne; Cardinale, Daniela; Carver, Joseph; Dent, Susan; Ky, Bonnie; Lyon, Alexander R; López-Fernández, Teresa; Fradley, Michael G; et al.
Abstract: The discipline of Cardio-Oncology has seen tremendous growth over the past decade. It is devoted to the cardiovascular (CV) care of the cancer patient, especially to the mitigation and management of CV complications or toxicities of cancer therapies, which can have profound implications on prognosis. To that effect, many studies have assessed CV toxicities in patients undergoing various types of cancer therapies; however, direct comparisons have proven difficult due to lack of uniformity in CV toxicity endpoints. Similarly, in clinical practice, there can be substantial differences in the understanding of what constitutes CV toxicity, which can lead to significant variation in patient management and outcomes. This document addresses these issues and provides consensus definitions for the most commonly reported CV toxicities, including cardiomyopathy/heart failure and myocarditis, vascular toxicity, and hypertension, as well as arrhythmias and QTc prolongation. The current document reflects a harmonizing review of the current landscape in CV toxicities and the definitions used to define these. This consensus effort aims to provide a structure for definitions of CV toxicity in the clinic and for future research. It will be important to link the definitions outlined herein to outcomes in clinical practice and CV endpoints in clinical trials. It should facilitate communication across various disciplines to improve clinical outcomes for cancer patients with CV diseases. Graphical Abstract: